MODEL OF TRANSMISSION COVID-19 USING SIQRD MODEL WITH THE EFFECT OF VACCINATION IN MATARAM - Febryantika, Annisa Zaen; Marwan, Marwan; Awalushaumi, Lailia; Syechah, Bulqis Nebulla (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2023)
Mathematical modeling is considered an effective tool for analyzing real-life problems. In this research, we analyze the dynamics of the COVID-19 spread in Mataram city using the SIQRD model with influence of the vaccination. The analyze based on varying some parameter values of the model i.e the transmission rate (β), the recovery rate for COVID-19 (γ), and the death rate (δ), before and after vaccination respectively. Our chosen methodology involves parameter estimation using the Euler method. The result shows that the model has an endemic equilibrium point which remains stable before and after vaccination. Furthermore, the basic reproduction number (R0) which states the number of secondary cases that occur if there are infected people in a population, has the value more than 1 before the vaccination, but equal to 1 after the vaccination. This suggests that prior to COVID-19 vaccination, infected individuals could potentially infect more than one person, but after vaccination, each infected person tends to only infect one other individual. This shift is attributed to the subsidence of COVID-19 symptoms following vaccination